Padrões globais e preditores da diversidade beta taxonômica e funcional em assembleias de peixes recifais - Maxwell, Melina Forgiarini (2020)
One of the main focuses of macroecological studies is to understand the spatial variation and, in addition, to evaluate which are the predictors that shape this variation among terrestrial, freshwater and marine ecosystems. Diversity can be measured by its taxonomic and functional value. Also, this diversity can be partitioned into alpha, beta and gama. Beta diversity corresponds to the difference of species composition or functional traits between pairs of communities e can be divided in turnover and nestedness components. Turnover is the substitution of species/functional traits between areas, being associated with species dispersal. Marine biodiversity can also be measured through variations of species and functions, that them perform. Reef areas are one of the main marine biodiversity centers in the world and have a high diversity of marine organisms, among them the reef fish. Reef fish corresponds to more than 6.000 species with a wide distribution throughout the oceans and it performs essential functions for the maintenance of reef ecosystems. The dissimilarity values between communities of tropical reef fish have been used to delimit biogeographic regions and to evaluate differences (i.e., beta diversity) in taxonomic, functional and phylogenetic compositions. Moreover, there is studies relating beta-diversity patterns to environmental variables at local and regional scales. Thus, the main aims of this dissertation are: (i) to investigate taxonomic and functional beta diversity patterns of reef fish assemblages on a global scale; (ii) to evaluate the congruence between taxonomic and functional and taxonomic beta diversity between pairs of reef fish assemblages; and (iii) to determine the relative importance of environmental predictors in patterns of taxonomic and functional beta diversity. Moreover, it is essential to know if the same predictor variables shape beta taxonomic and functional diversity in different realms and biogeographic regions.